PSYCHIATRIC MANIFESTATIONS AND MENTAL HEALTH PROFILES IN INDIVIDUALS WITH VITILIGO - Rajapov M.Sh. (Web of Journals Publishing, 2025)
Vitiligo is one of the most common skin diseases and is diagnosed by a chronic relapsing course with increasing severity, having a long chronic course that continues through life. The proportion of psychogenic ally-provoked exacerbations of vitiligo developing during life was determined by studying a representative sample of sick.
Keywords: vitiligo, psychogenic, path characterological deviations, comorbidity, affective disorders